Brief intervention to prevent HIV, STI and unintended pregnancies: preliminary results of a feasibility study from the perspective of healthcare providers in Peru - Jean Pierre Jiron; Clara Sandoval; Juan Carlos Enciso; Ana Sofía De Vasconcelos; Karel Blondeel; Nataliia Bakunina; Galina Lesco; Igor Toskin; Rob Stephenson; Carlos F. Caceres (BMC, 2021)
Abstract Background Brief interventions have proven to be valuable instruments for the treatment and care of clients with diverse health needs, due to their potential to impact both the individual and the population. In this regard, the Brief Sexuality-Related Communication (BSC) is presented as a viable and effective alternative for addressing sexual and reproductive health problems, assessing risk behaviors and motivating clients to generate behavioral change. Since health providers are key actors in treatment and prevention, it is essential to know their perceptions about the BSC intervention, as well as its acceptability in different contexts, with diverse client populations. Thus, the following paper reflects the findings of the perceptions and experiences of health providers in Peru from the first phase of the Feasibility study of a BSC intervention to prevent STIs and unintended pregnancies. Methods This is the first phase of a multisite and multiphase study of the feasibility of a BSC intervention. We conducted twenty in-depth interviews (IDI) with health care providers (physicians, obstetricians, psychologists, nurses and peer counselors) recruited from three health care institutions in Peru: The Tahuantinsuyo Bajo Maternal and Child Center (CMI) and the San José Maternal and Child Center, both located in the capital city, Lima; and La Caleta Hospital located in Chimbote, northern coast of Peru. Participating health providers included those working at the HIV/STI Reference service and the family planning/reproductive health service. The IDI addressed three domains: 1) Acceptability of the BSC intervention; 2) Perceived willingness to implement the BSC intervention; and 3) Considerations for the Implementation of the BSC intervention. Results Health providers expressed high acceptance of the BSC intervention, considering it as a useful and effective instrument to address sexual and reproductive health problems with all clients; however, some providers had some concerns about the real impact of the intervention to achieve significant behavior change. On the other hand, health providers showed high willingness to learn and implement the BSC intervention, affirming their commitment to learn new techniques and strategies that could allow them to improve their knowledge and the quality of their care. Health care providers consider it necessary to take into account the barriers that arise in the implementation of the BSC intervention, such as the structural limitations to access, the providers' abilities to deliver the intervention effectively, and the participants' reception of the intervention. Finally, providers consider it essential to establish the BSC intervention in a normative framework that allows it to receive the support of the health departments and eventually enforces implementation. Conclusions Health providers consider the BSC intervention as an interesting and exciting behavioral intervention to deal with the sexual and reproductive health issues existing in different populations, and seemed highly willing to adapt and implement it, hoping that it become beneficial to all client populations to prevent HIV/STIs and unintended pregnancies.